Advertising: principles and practice - Wells, Williams; Burnett, John; Moriarty, Sandra (New Jersey: Prentice Hall, 1995)
Contents: part 1: advertising foundations and environment. cap. 1. introduction to advertising. 2. advertising and society: ethics and regulation. 3. advertising and the marketing process .4. advertising agencies. art 2: advertising background, planning, and strtegy. cap 5. the consumer audience. 6. strategic research. 7. trategy and planning .8. how advertising works. Part 3. : advertising media. part 4 : theating advertising. part 5. advertising operations. part 6. miscellaneous advertising.
Keywords: Marketing - Publicidad